Importance of Lid Hygiene Before Ocular Surgery: Qualitative and Quantitative Analysis of Eyelid and Conjunctiva Microbiota. Issue 6 (November 2016) - Peral, Assumpta; Alonso, Jose; García-García, Concepción; Niño-Rueda, Cristina; Calvo del Bosque, Patricia
Abstract : Objective: To evaluate the efficacy of a cleansing eyelid wipe in reducing the microbiota present on the ocular surface before cataract surgery. Methods: A single-center, prospective, single-blind phase IV study was conducted at the University Complutense of Madrid. Forty-five adult patients who were scheduled for ocular surgery after treatment with commercially available eyelid wipes were consecutively enrolled. The study lasted 5 days and the patients were examined at day 0 (D0), day 3 (D3), and day 5 (D5). They received instructions to apply the eyelid wipe only to the eye subject to surgery, using the other eye as a control with no treatment. Lid and conjunctival swabs were taken on each day and microbes identified. Ocular surface microbiota was estimated by measuring the area of the agar plate occupied by the grown colonies with respect to the total available area. Results: Measurements at D3 and D5 showed a percent reduction of 58% and 63%, respectively, in the microbial load on the eyelid in the treated eyes ( P =0.0011). There was also a reduction, although nonsignificant, in the microbiota of the conjunctiva of 72% and 69% on D3 and D5, respectively. Conclusions: The degree of microbiota reduction was comparable with that obtained after topical application of antibiotics in other studies. The results suggest the use of these eyelid wipes as a complementary prophylactic method before any ocular surgery.